Implementation of the project based learning (PjBL) model assisted by picture word card media to improve write beginning ability student first grade elementary school - Nurlatifah, Risa; Sukma Murni, Sukma (Current Issues on Elementary Education Journal, 2023)
This research was conducted to find out the scenarios and implementation of the application of learning, student responses and improving student learning outcomes on preliminary writing skills using the Project Based Learning (PjBL) learning model assisted by picture word card media. This research uses the Classroom Action Research method. The sample is 15 students of Class 1 at SDN 222 Pasirpogor. This research was conducted through two action cycles. The results showed that the implementation of learning received a positive response from students in the first and second cycles with a percentage of 90% and 87%. Learning outcomes also increased from cycle I to cycle II, showing the percentage of 66% and 86% achieving the minimum completeness criteria. This research concluded that through the Project Based Learning (PjBL) model assisted by media with picture word cards, students' preliminary writing ability increased.